Normative account of Islamic bioethics in end-of-life care. Issue 1 (31st December 2022) - Elmahjub, Ezieddin
ABSTRACT: This article addresses the bioethical challenges raised by end-of-life care (EoLC) from the perspective of Islamic normativity. Rejecting positivist positions, it argues for the use of a flexible approach midway between a deontological conception of human life as having a sacred value that cannot be bargained over, as represented by the teachings of Abū Ḥāmid al-Ghazālī's, and one that introduces considerations of pain (alam) and pleasure (ladhdah) into ethical evaluations, as expounded by the jurist Fakhr al-Dīn al-Rāzī. Under this approach, described as "Islamic evaluator relativity, " moral agents formulate a normative position tailored to their beliefs and the circumstances of the case, in which the right course of action is expressed as a value judgement (amr ijtihādi) and the evaluator (mujtahid) is rewarded regardless of the choices they make. Keywords: Islamic bioethics, End-of-life-care, bioethics, normative ethics.